Assessment Of The Equilibration Of Occlusion And Periodontal Ligament Changes Following The Placement Of Stainless Steel Crown Using Hall Technique In Children By Intra Oral Digital Radiography-An In Vivo Study - Dr. Alisha T Susan; Dr.Amith Adyanthaya; Dr.Karthik Nair; Dr.Anju R V; Dr Aiswarya M V; Dr. Hanna Kizhakayil Hafiz; Dr. Jadeera N A; Dr . Krishna N S (The Bioscan, 2026)
Background: The Hall technique in pediatric dentistry simplifies stainless steel crown placement by avoiding caries removal and tooth preparation. However, the biological basis of occlusal equilibration involving the periodontal ligament (PDL) and alveolar bone remains underexplored. Aim: To evaluate the mechanism of occlusal settling following stainless steel crown placement using the Hall technique in children.